Graphitic carbon nitride catalysed photoacetalization of aldehydes/ketones under ambient conditions. Issue 13 (14th January 2016) - Abdullah Khan, M.; Teixeira, Ivo F.; Li, Molly M. J.; Koito, Yusuke; Tsang, Shik Chi Edman
Abstract : Photoacetalization of aldehydes/ketones with alcohols over graphitic carbon nitride is demonstrated without any acid additive. Abstract : Graphitic-C3 N4 is shown for the first time to catalyse photoacetalization of aldehydes/ketones with alcohols to acetals in high yields using visible light under ambient conditions; transient charge separation over the material is effective to catalyse the reaction in the absence of Lewis or Brønsted acids, giving a new green alternative catalyst.